A escola e a cidade: cartografia da educação física escolar, uma proposta educativa para oportunizar aos alunos experiências em espaços públicos da cidade - Washington Luis Moreira Vieira (2023)
This work aimed to understand the context in which students of the fifth year of Elementary School, from a public school in the municipality of Iguaba Grande-RJ are inserted, relating the right to access spaces in this city to provide opportunities for bodily experiences, through a Didactic Unit focused on Games and Games. With this study, we sought to answer some guiding questions that provided greater support in the discussion with the results obtained: What is the relationship that the students of the Escola Municipal Paulino Pinto Pinheiro Filho have with the city they live in? What spaces in this city do they have the right to access and also attend? How did these students behave in experiences of activities outside the school environment? After presenting the research and signing the terms of assent and consent for participation in the work, a questionnaire was applied in order to be able to collect data to give more consistency and further support the discussion, where students exposed the places where they live, as well as the public spaces in the city that they frequent, and the Games and Games that they are more familiar with. After that, we chose the edge of Laguna de Araruama to experience the aforementioned Didactic Unit. To contribute to data analysis, we used the cartographic method, in addition to participant observation. After carrying out the activities outside the school environment, the students made experiential maps through drawings about the experience they had in the research and in relation to the city that each one lives. Finally, an exhibition was held in which these photographs and drawings were displayed at the institution in December 2022, where students from other classes had the opportunity to visit and experience some activities proposed in the Didactic Unit. The photographs, maps, and games and games experienced are available on the website https://aescolaeacidade.my.canva.site/.